2021
DOI: 10.1038/s41598-020-78910-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene diversity explains variation in biological features of insect killing fungus, Beauveria bassiana

Abstract: Beauveria bassiana is a species complex whose isolates show considerable natural genetic variability. However, little is known about how this genetic diversity affects the fungus performance. Herein, we characterized the diversity of genes involved in various mechanisms of the infective cycle of 42 isolates that have different growth rates, thermotolerance and virulence. The analysed genes showed general genetic diversity measured as non-synonymous changes (NSC) and copy number variation (CNV), with most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
1
9
0
1
Order By: Relevance
“…reported that B. bassiana ERL836 highly activated two metabolic pathways: plasma membrane‐mediated transportation and fatty acid degradation, by catalysis of cytochrome P450. Recent studies of genetic diversity have indicated that lectin‐like, mucin‐induced signaling‐associated, biotrophy‐associated, and chitinase genes were required for the EPFs' virulence 43 . It should be determined whether or not the genes described above contributed to the rapid Bb ‐eGFP conidial adhesion, germination, germ tuber formation, production of penetration peg (a kind of hypha), and early penetration of the T. castaneum larval body cuticles.…”
Section: Resultsmentioning
confidence: 99%
“…reported that B. bassiana ERL836 highly activated two metabolic pathways: plasma membrane‐mediated transportation and fatty acid degradation, by catalysis of cytochrome P450. Recent studies of genetic diversity have indicated that lectin‐like, mucin‐induced signaling‐associated, biotrophy‐associated, and chitinase genes were required for the EPFs' virulence 43 . It should be determined whether or not the genes described above contributed to the rapid Bb ‐eGFP conidial adhesion, germination, germ tuber formation, production of penetration peg (a kind of hypha), and early penetration of the T. castaneum larval body cuticles.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al (2020) examined the genetic difference among B. bassiana isolates from different hosts by phylogenetic analysis and determined genetic differences between the virulent isolates. In a more recent study, Gasmi et al (2021) characterized the variety of genes involved in diverse mechanisms of the infective cycle of 42 isolates that have different thermo-tolerance, growth rates, and virulence. The analyzed genes showed general genetic diversity measured as and copy number variation (CNV) and non-synonymous changes (NSC) with most of them being subjected to positive episodic diversifying selection.…”
Section: Discussionmentioning
confidence: 99%
“…Be. bassiana sensu stricto is generally recognised as a globally distributed, genetically diverse species or species complex [69,70].…”
Section: Discussionmentioning
confidence: 99%